2021
DOI: 10.1038/s41598-021-83757-1
|View full text |Cite
|
Sign up to set email alerts
|

Green tea extracts containing epigallocatechin-3-gallate modulate facial development in Down syndrome

Abstract: Trisomy of human chromosome 21 (Down syndrome, DS) alters development of multiple organ systems, including the face and underlying skeleton. Besides causing stigmata, these facial dysmorphologies can impair vital functions such as hearing, breathing, mastication, and health. To investigate the therapeutic potential of green tea extracts containing epigallocatechin-3-gallate (GTE-EGCG) for alleviating facial dysmorphologies associated with DS, we performed an experimental study with continued pre- and postnatal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
39
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 26 publications
(43 citation statements)
references
References 48 publications
1
39
3
Order By: Relevance
“…Changes in other domains have been investigated. Facial dysmorphology was improved in DS mouse models and also observed in young children treated with GTE-EGCG [230,232]. Nevertheless, Stringer et al [215] stressed the negative effect on long bones development in treated mice.…”
Section: Discussionmentioning
confidence: 99%
“…Changes in other domains have been investigated. Facial dysmorphology was improved in DS mouse models and also observed in young children treated with GTE-EGCG [230,232]. Nevertheless, Stringer et al [215] stressed the negative effect on long bones development in treated mice.…”
Section: Discussionmentioning
confidence: 99%
“…Another recent trial showed that EGCG modulates facial development with dose-dependent effect if administered at low doses (30 mg/kg/day) before the age of three. Higher doses (100 mg/kg/day) would potentially have detrimental effects [107].…”
Section: Effects Of Catechins On Down Syndrome (Ds) Neurocognitive Disordersmentioning
confidence: 99%
“…A recent cross-sectional study of Starbuck et al (2021) investigated if green tea extracts with EGCG could modulate facial dysmorphologies DS [110]. These facial dysmorphologies can impair vital functions such as hearing, breathing, mastication, and health.…”
Section: Egcg In Relation To Cognitive Functioning Facial Shape and Body Weightmentioning
confidence: 99%